The Influence of Government Expenditure and Economic Growth on the Human Development Index in Timor-Leste (2008–2022) - Ivonia Auxiliadora Freitas Marcal; Arga Christian Sitohang (Indonesian Journal Publisher, 2025)
This study investigates the influence of Government Expenditure and Economic Growth on the Human Development Index (HDI) in Timor-Leste over the period 2008–2022. The analysis employs annual time-series data and utilizes a semi-log multiple linear regression model to accommodate differences in measurement scales among variables. Descriptive results reveal substantial fluctuations in Government Expenditure and Economic Growth driven by fiscal pressures, political instability, and external shocks such as the COVID-19 pandemic. In contrast, HDI demonstrates a gradual upward trend, reflecting the long-term nature of human development indicators. Empirical findings show that Government Expenditure and Economic Growth jointly exert a significant influence on HDI. However, partially, Government Expenditure displays a significant negative effect, suggesting inefficiencies in budget allocation or delayed policy impacts on social outcomes. Meanwhile, Economic Growth exhibits a negative but statistically insignificant effect, indicating that economic expansion, largely driven by the oil and gas sector, has not translated into meaningful improvements in human development. The model’s coefficient of determination (R² = 0.5545) indicates that 55.45% of the variation in HDI is explained by the included variables, while the remaining 44.55% is influenced by structural factors such as institutional capacity, public service quality, income distribution, and access to education and health services. Overall, the study underscores the importance of enhancing public expenditure effectiveness and promoting inclusive economic growth to strengthen human development outcomes in Timor-Leste.